Short thermal annealing for crystallization of plasma-CVD amorphous silicon films - Yasuhiro Matsumoto (Superficies y vacío, 2000)
The possibility of obtaining acceptable crystallization time and high-quality poly-Si by using PECVD depositedamorphous silicon films with silane has been explored. The film structure has been investigated by x-ray diffraction andRaman spectroscopy as a function of annealing temperature. For samples annealed only 10 minutes, we found a sharpconductivity increment of about tree orders of magnitude for temperatures near and above 780°C. The x-ray diffractionfor samples treated at 850°C, clearly shows crystalline phases along the <111>, <220> and <311> Si crystallographicdirections in the case both c-Si and quartz substrates. This means, despite the short thermal annealing time, that theformed poly-Si textures are very similar to those made utilizing long-time crystallization procedures